When fashion is not just fashion: the place of fashion in Simmel’s sociology - Barbosa, Carlos Alberto (2021)
Considering the references to Georg Simmel’s essay Fashion (2020) made by Crane (2006), Erner (2005), Lipovetsky (2009), and Svendsen (2010), this article discusses Simmel’s theory of fashion as a social phenomenon transcending the aspects linked to the imitation mechanism, known as trickle-down theory. In this sense, the article focuses on the references that Crane (2006) makes to Simmel’s essay since the author points out that the study on imitation would have been Simmel’s main contribution to a sociology of fashion. Her focus on the trickle-down theory isolates and displaces the aspect of imitation from other theoretical developments carried out by Simmel, such as the theoretical and methodological grounds of interaction and the forms of socialization. This displacement of Simmel’s theory ends up shading part of the critical elements that he unfolds about fashion in its ephemeral condition,typical of the author’s modernity discussion in the 19th century.